Calcium-Related Gene Signatures May Predict Prognosis and Level of Immunosuppression in Gliomas - Liu, Peidong; Li, Yu; Zhang, Yiming; Choi, John; Zhang, Jinhao; Shang, Guanjie; Li, Bailiang; Lin, Ya-Jui; Saleh, Laura; Zhang, Liang; Yi, Li; Yu, Shengping; et al. (Frontiers in Oncology, 2022)
Gliomas are the most common primary brain cancer. While it has been known that calcium-related genes correlate with gliomagenesis, the relationship between calcium-related genes and glioma prognosis remains unclear. We assessed TCGA datasets of mRNA expressions with differentially expressed genes (DEGs) and enrichment analysis to specifically screen for genes that regulate or are affected by calcium levels. We then correlated the identified calcium-related genes with unsupervised/supervised learning to classify glioma patients into 2 risk groups. We also correlated our identified genes with immune signatures. As a result, we discovered 460 calcium genes and 35 Calcium Key Genes that were associated with OS. There were 13 DEGs between Cluster½ with different OS. At the same time, 10 Calcium Hub Genes (CHGs) signature models were constructed using supervised learning, and the prognostic risk scores of the 3 cohorts of samples were calculated. Risk score was confirmed as an independent predictor of prognosis. Immune enrichment analysis revealed an immunosuppressive tumor microenvironment with upregulation of checkpoint markers in high-risk group. Finally, a Nomogram was generated with risk scores and other clinical prognostic independent indicators to quantify prognosis. Our findings suggest that calcium-related gene expression patterns could be applicable to predict prognosis and predict levels of immunosuppression.